PENGARUH KONTROL DIRI TERBADAP PERILAKU MENYIMPANG PESERTA DIDIK KELAS VllI Dl SMP NEGERI26 PADANG - Yulni, Misri - (Bimbingan dan Konseling, 2014)
Â This research is motivated by the phenomenon that researchers found during the practice field. Based on this phenomeno" the researchers raised the issue of research on the influence of self-control to misbehavior in the eighth grade students of SMPN 26 Padang. This type of research is descriptive quantitative method . The population of this research is class VITI students numbered 266 people. The samples in this study using proportional sampling technique. From the calculation results obtained sample of 68 people. The instruments used in the study were a questionnaire. To analyze the data used simple linear regression formula in order to see the effect of self-control to misbehavior of students in class Vlll. The results of data analysis showed that:(I) A description of self-control students in the category quite well . (2) A description to misbehavior of learners is in the category of very many. (3) The effect of self-controlmisbehavior is obtained . So the results. the effect of self-control to misbehavior of students in class vmSlfPN 26 Padang with the degree of influence is strong enough.